The Financial Technologies Utilization to Increase the Competitive Advantage of Product Marketing - Lilis Sugi Rahayu Ningsih; Lik Anah (Jurnal Economic Resource, 2021)
This research aimed to determine the effect of financial technologies utilization to increase the competitive advantage of product marketing at the MSME (micro, small, and medium enterprise) micro community Go Nganjuk on facing the 2019 corona virus disease pandemic (COVID-19) by using multiple linear regression analysis method which is strengthened by qualitative analysis. Determination of sample of 40 respondents with a total population of 250 respondents. The result of the study through the distribution of questionnaires and using reliability and validity tests, as well as classical assumption test, which consisting of normality test and heteroscedasticity test, there is an effect of financial technology utilization in the competitive advantage of product marketing. Indicators that affect the financial technology variable. Concluding the results of the study that the maximum use of financial technology can increase competitive advantage in product marketing activities at the MSME Micro Community GO Nganjuk.